Psychometric validation of the Spanish alopecia areata–life impact questionnaire - Muñoz-Barba, Daniel; García-Moronta, Carmen; Limeres-De la Rosa, Miguel; Sánchez-Díaz, Manuel; Arias-Santiago, Salvador (Frontiers in Medicine, 2025)
IntroductionAlopecia areata (AA) is a chronic immune-mediated disorder associated with substantial psychosocial burden. Generic dermatology instruments, such as the DLQI, may fail to capture AA-specific concerns, prompting the development of targeted questionnaires like the AA-QLI. However, existing tools show methodological limitations and inconsistent use. This study aimed to validate the Spanish Alopecia Areata–Life Impact Questionnaire (SAALIQ) by assessing its reliability, validity, and responsiveness, providing a robust instrument for evaluating the quality-of-life (QoL) impact of AA in Spanish-speaking patients.MethodsA single-center cross-sectional study was conducted between June 2024 and June 2025. Adults with AA, recruited sequentially regardless of disease severity, duration, or prior treatments, were included. QoL was assessed using generic and disease-specific questionnaires, including the SAALIQ, developed in collaboration with the Alopecia Association of the Community of Madrid. Psychometric validation included assessment of internal consistency, test–retest reliability, and convergent validity. Receiver-operating characteristic (ROC) analyses were performed to determine cut-off points.ResultsA total of 85 patients with AA were included (72.94% women, 27.06% men) with a mean age of 37.55 years. The mean disease duration was 10.12 years, and the mean baseline SALT score was 36.52%. Cronbach’s α ranged from 0.73 to 0.80 across emotional, functional, and social domains. Intraclass correlation coefficient (ICC) for the total score was 0.947. Convergent validity was confirmed by moderate-to-strong correlations with DLQI, Hospital Anxiety and Depression Scale (HADS-A, HADS-D), and a strong correlation with the AA-QLI (r = 0.603; ρ = 0.714; p < 0.0001). Greater SAALIQ scores were observed in women, in patients with AA totalis (AAT) or multiple patch involvement, and in those with longer disease duration (p < 0.05). ROC analysis identified SAALIQ cut-offs of <20 for absent/mild, ≥20 for moderate, and >26 for severe QoL impairment.ConclusionThe SAALIQ is a disease-specific and culturally adapted tool that enables accurate measurement of the QoL impact of AA in Spanish-speaking patients. Its psychometric performance, validated cut-off points, and ability to capture domains overlooked by generic measures make it an essential resource for patient-centered care, clinical trials, and international research. Further studies are warranted to confirm the generalizability of our findings.